Impact of long term integrated nutrient management system on soil health and rice productivity - Rakhi R (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2017)
The investigation ‘Impact of long term integrated nutrient management system on soil health and rice productivity’ was conducted at Integrated Farming Systems Research Station, Karamana, during kharif and rabi, 2016-’17, with medium duration rice variety Uma, to assess the impact of long term integrated nutrient management practices on soil physical, chemical and biological properties, soil organic carbon and to study their impact on rice productivity. The experiment was laid out in a randomized block design with three replications and twelve treatments viz. absolute control (T1), 50% RDN as fertilizers during kharif and rabi (T2), 50% RDN as fertilizers during kharif and 100% RDN as fertilizers during rabi (T3), 75% RDN as fertilizers during kharif and rabi (T4), 100% RDN as fertilizers during kharif and rabi (T5) and substitution of 50% and 25% of RDN on nitrogen equivalent basis through organic manures viz. FYM (T6 and T7), crop residues (T8 and T9) and green manure (T10 and T11) during kharif and 100% and 75% RDN as fertilizers respectively during rabi and a farmer’s practice (T12). The soil of the experimental site before kharif 2016 was strongly acidic in reaction, sandy clay in texture, low in CEC, high in organic carbon, low in available N, high in available P, medium in available K, sufficient in available, S, Fe, Mn, Cu, Zn and exchangeable Ca and deficient in available B and exchangeable Mg. Substitution of up to 25 to 50 per cent RDN either with FYM, crop residues or green manure gave yield either higher or on par with 100 per cent inorganic treatment. Substitution of 25 per cent RDN with FYM (T7) gave the highest grain system productivity which was significantly higher than 100 per cent inorganic treatment. The number of productive tillers per hill and number of grains per panicle for the INM treatments were on par with 100 per cent inorganic treatment for both seasons. T6 recorded the highest per cent filled grains during both kharif and rabi. The application of recommended doses of fertilizers alone (T5) resulted in lower uptake of N, P and K when compared to conjunctive use of 25 to 50 per cent RDN substituted either with FYM, crop residues or green manure. Integrated use of organics and inorganics also resulted in higher uptake of Ca, Mg and micronutrients (Fe, Mn, Cu, Zn and B) by grain and straw during both seasons over the purely inorganic treatments and the absolute control. Long term INM treatments also improved the physical properties of the soil by decreasing the bulk density and improving the WHC significantly over the other treatments. Soil pH showed a significant decrease after kharif in treatments where organic manures were applied compared to the inorganic treatments. EC of the soil was not influenced significantly due to different treatments during both the crop seasons. Organic carbon content and CEC of the soil were highest in treatment T6 receiving 50% RDN through inorganic fertilizers and 50% N through FYM during kharif followed by 100% RDN during rabi. Available N and K in soil did not show any significant difference between INM and 100% inorganic treatment. Soil available P was generally higher for all the treatments with significantly higher values for the 25 per cent FYM substituted treatment. Higher values for available B was observed for the treatments receiving 50 per cent substitution of fertilizers through organic manures compared to the other treatments. However, integrated treatments failed to show any consistent variation in exchangeable Ca and Mg, available S, Fe, Mn, Cu and Zn in soil over the other treatments. Studies on microbial population and enzyme activities revealed the positive influence of integrated nutrient management on soil biological properties over inorganic treatments. Population of bacteria, fungi, actinomycetes and Azospirillum were found to be higher for treatments involving substitution of fertilizers with organics either at 25 or 50 per cent. Urease and acid phosphatase activity were generally improved due to the substitution of inorganics by organics to the extent of 50 per cent. Economic analysis revealed the superiority of integrated nutrient management over purely inorganic treatments and significantly higher B:C ratio was exhibited by the treatment receiving 25 per cent substitution of RDN with FYM during kharif and 75 per cent RDN through fertilizers during rabi compared to T5. All INM treatments gave B:C ratio on par with T5. From the experiment, it was found that substitution of RDN up to 25 to 50 per cent gave grain yield either on par or significantly higher than the 100 per cent inorganic treatment. To achieve the maximum returns and highest productivity, 25 per cent nitrogen must be substituted as FYM during kharif and 75 per cent nutrients applied as fertilizers during rabi. Substitution of organic manures for inorganics has beneficial effect on soil health by improving physicochemical and biological properties and nutrient availability and resulting in enhanced grain and straw yield. Thus judicious substitution of organic manures for fertilizers can improve the yield in a rice-rice cropping system. It can also save 25 per cent of fertilizers during both seasons or 50 per cent fertilizers during kharif without any reduction in yield.